Siloed Diversity Transnational Migration, Digital Media and Social Networks - Gomes, Catherine (Springer Singapore, 2018)
This book examines the experiences of transient migrants in the Asia-Pacific, and in so doing provides new ways of understanding diversity. By focusing on the transient destination hubs of Australia and Singapore, Catherine Gomes shifts our thinking about diversity for two disruptive reasons: the increasingly large and global transient flows of people and our everyday reliance on digital media. The unprecedented usage of digital media influences not only communication patterns and information-seeking behaviour, but has also led to the rapid evolution of the very nature of entertainment and news, and directly impacted on our documenting and mapping of self (e.g. posts of photographs, opinions and links on social media timelines). The book introduces readers to the concept of siloed diversity - a phenomenon which occurs when people rely on a hierarchy of identities developed while in transience to make connections and disconnections with others.